KREATIFITAS MAHASISWA DALAM MENYELESAIKAN SOAL TERBUKA PADA MATERI VEKTOR - Zukhrufurrohmah Zukhrufurrohmah (Yayasan Pendidikan Intan Cendekia, 2018)
Creativity is the important thing that have been used to solve and face a problem. Training the creativity continue to be made to improve the ability to solve problems. This research aims to describe the upperclassmen college student’s creativity in solving the open ended problem in vector material. This research measure the mathematical creativity by indicators based on the aspect of fluency, flexibility, originality. The qualitative research was done with the first step, identification of the phenomenon, the creativity of students in resolving the open ended problem of vector material. Second, the identification of the subject, 41 upperclassmen college students. Third, hypothesis, how to solve the open ended problem of vector can describe the creativity of the students. Fourth, collecting the data, the results of the student's answer and the data were analyzed using critical thinking indicators. Fifth, interpretations and conclusions, using indicators to describe the results of the work of students and conclude. The results showed 10% of students are creative in solving a given problem because convenient these three aspects of creativity that has been set, 22% of the students are said to be creative enough because it convenient meets the two aspects of the third aspects of the set, and 68% of students including categories less creative because it convenient less than or equal to one aspect of the three aspects. Summary obtained suggests that aspects of the least convenience is the aspect of flexibility which suggests that the student cannot present more than one different way.